Multiple Systemic Embolic Complicating the Course of a Patient with an Atrial Septal Defect, an Atrial Septal Aneurysm and an Endocardial Right Atrial Pacemaker Lead - Johnson, Charles; Galindez, Laura (Puerto Rico Health Sciences Journal, 2016)
see manuscript